Household pesticides and their practices in Dhaka City - Sultana, Afroza; Raheman, Magfur; Hossain, Mosharraf (Bangladesh Journal of Zoology, 2015)
Abstract not available Bangladesh J. Zool. 43(1): 137-139, 2015